Comparison of the reduction in blood glucose levels of mice (mus musculus) given boiled water from ginger (zingiber officinale) with metformin - Ida Royani; Aining Rezkyana; Rezky Putri Indarwati Abdullah; Irmayanti Haidir Bima; Febie Irsandy Syahruddin (Sean Institute, 2024)
Elevated blood sugar levels that exceed the established normal limits are a typical symptom of diabetes, a metabolic disorder. Traditional medicine is said to have fewer side effects than modern medicine, which has led to its long history of being favored by many people diagnosed with diabetes. People often use ginger as an herbal remedy for hypoglycemia. Ginger can be used as a natural antidiabetic drug due to the antiglycemic effect of its flavonoid content. To determine the comparison of blood glucose levels of mice (Mus musculus) given water decoction of ginger (Zingiber officinale) with metformin.Experimental research with pre and post test randomized controlled group design There was a decrease in the average blood glucose level of mice (Mus musculus) given water decoction of ginger (Zingiber officinale), from ±185.5 mg/dL to ±136.17 mg/dL, but not as good as metformin, which decreased from ±191 .17 mg/dL to ±108.67 mg/dL. Water decoction of ginger (Zingiber officinale) can reduce fasting blood glucose levels in mice (Mus musculus) although not as well as mice (Mus musculus) given metformin.